2020
DOI: 10.3390/safety6040052
|View full text |Cite
|
Sign up to set email alerts
|

Health, Physical Activity and Musculoskeletal Symptoms among Stone, Sand, and Gravel Mine Workers: Implications for Enhancing and Sustaining Worker Health and Safety

Abstract: There is little data delineating relationships between health and worker musculoskeletal symptoms (MSS), particularly among stone, sand, and gravel mine (SSGM) workers. There is also little data detailing the relationships between physical activity and MSS among these workers. A cross-sectional study using data from 459 SSGM workers was completed. Logistic regression analyses assessed relationships between health factors, physical activity, and low back, neck, shoulder, and knee MSS. Those who reported their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This perception is supported by current research. Smith and colleagues found that SSGM workers who reported their health as very good to excellent were less likely to suffer low back and knee musculoskeletal symptoms and those who were considered obese were more likely to experience knee musculoskeletal symptoms (T. D. Smith et al, 2020). Potential programs to bolster fitness within the industry may include what two different participants termed "stretch and flex" programs.…”
Section: Safety Resources and Protective Factorsmentioning
confidence: 99%
“…This perception is supported by current research. Smith and colleagues found that SSGM workers who reported their health as very good to excellent were less likely to suffer low back and knee musculoskeletal symptoms and those who were considered obese were more likely to experience knee musculoskeletal symptoms (T. D. Smith et al, 2020). Potential programs to bolster fitness within the industry may include what two different participants termed "stretch and flex" programs.…”
Section: Safety Resources and Protective Factorsmentioning
confidence: 99%
“…A two-step system of the work task assessment is used: The first step includes the assessment of the working posture of the individual body parts using angles. The second step includes the conditions which in the first step were labelled as conditionally acceptable or as acceptable [45][46][47][48][49][50].…”
Section: Assessment Of Work Positionsmentioning
confidence: 99%
“…The definition of a conditionally acceptable position of the trunk, head and neck, and upper and lower limbs is shown in Steps 1 and 2. The total time during an 8-h shift in each conditionally acceptable working position must not exceed 160 min, and the duration of the individual tasks must not be longer than 1 to 8 min depending on the type of the position and movement frequency [45][46][47][48][49][50].…”
Section: Assessment Of Work Positionsmentioning
confidence: 99%
See 2 more Smart Citations